7th International Electronic Conference on Sensors and Applications 2020
DOI: 10.3390/ecsa-7-08243
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Piezoelectric Sensors Applied to Multiple Partial Discharge Detection by Advanced Signal Processing Analysis

Abstract: The development of sensors applied to failure detection systems for power transformers is a critical concern since this device stands out as a strategic component of the electric power system. Among the most common issues is the presence of partial discharges (PDs) in the insulation system of the transformer, which can lead the device to total failure. Aiming to prevent unexpected damages, several PD monitoring approaches have been developed. One of the most promising is the Acoustic Emission (AE) technique, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Acoustic methods are widely recognized as capable of detecting partial discharges, as described in the IEC TS 62748:2016 international standard [ 53 ]. They often use piezoelectric sensors jointly with suitable signal processing approaches [ 54 , 55 ]. For the detection and location of corona discharges, an NL sonic camera has been used, whose main characteristics are summarized in Table 2 .…”
Section: The Analyzed Sonic and Dslr Camerasmentioning
confidence: 99%
“…Acoustic methods are widely recognized as capable of detecting partial discharges, as described in the IEC TS 62748:2016 international standard [ 53 ]. They often use piezoelectric sensors jointly with suitable signal processing approaches [ 54 , 55 ]. For the detection and location of corona discharges, an NL sonic camera has been used, whose main characteristics are summarized in Table 2 .…”
Section: The Analyzed Sonic and Dslr Camerasmentioning
confidence: 99%
“…The general acoustic localization method involves the use of piezoelectric transducers (PZTs) that are magnetically attached to the metal shell of the transformer tank [8]. The position of the partial discharge source is inferred by utilizing the time difference between the arrival of ultrasonic signals generated by partial discharge at different piezoelectric transducers [4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Partial discharges (PDs) are low-energy ionization processes that occur due to a local field concentration in a dielectric material [3]. On the other hand, full discharges (FDs) perform the complete disruption of the dielectric and can occur permanently or in random periods [4][5][6]. PDs and FDs are characterized as electric non-conformities that emit UV radiation, current pulses, and acoustic and electromagnetic waves, causing a progressive deterioration of the insulation components.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental tests, full discharges were induced in an oil-filled transformer, and the current signals produced by the Rogowski coils were compared using Power Spectrum Density (PSD) [2]. The Short-Time Fourier Transform (STFT) [6] was applied to detect repetitive discharges. The results indicated that the Ferrite core demonstrates high sensitivity in the frequency band between 0 and 1 MHz.…”
Section: Introductionmentioning
confidence: 99%